2021
DOI: 10.12688/wellcomeopenres.15931.2
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilisation and mortality outcomes in international migrants to the UK: analysis protocol for a linked population-based cohort study using Clinical Practice Research Datalink (CPRD), Hospital Episode Statistics (HES) and the Office for National Statistics (ONS)

Abstract: An estimated 14.2% (9.34 million people) of people living in the UK in 2019 were international migrants. Despite this, there are no large-scale national studies of their healthcare resource utilisation and little is known about how migrants access and use healthcare services. One ongoing study of migration health in the UK, the Million Migrants study, links electronic health records (EHRs) from hospital-based data, national death records and Public Health England migrant and refugee data. However, the Million … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The initial eligible cohort comprised individuals of all ages registered before January 2021, for any length of time, at a CPRD GOLD GP practice in the UK that was contributing ‘up-to-standard’ data (see Supplementary Box 2 for details) for any length of time in the January 2021 database build. 21 We reduced this initial cohort to individuals registered at a GP practice in England who were eligible for all linkages pre-specified in the study protocol 22 and we identified migrants by applying the migration code list. To comply with CPRD's data minimisation policy, we randomly sampled non-migrants from the reduced initial cohort at a ratio of 1:4 migrants to non-migrants and then linked this cohort to IMD data.…”
Section: Methodsmentioning
confidence: 99%
“…The initial eligible cohort comprised individuals of all ages registered before January 2021, for any length of time, at a CPRD GOLD GP practice in the UK that was contributing ‘up-to-standard’ data (see Supplementary Box 2 for details) for any length of time in the January 2021 database build. 21 We reduced this initial cohort to individuals registered at a GP practice in England who were eligible for all linkages pre-specified in the study protocol 22 and we identified migrants by applying the migration code list. To comply with CPRD's data minimisation policy, we randomly sampled non-migrants from the reduced initial cohort at a ratio of 1:4 migrants to non-migrants and then linked this cohort to IMD data.…”
Section: Methodsmentioning
confidence: 99%
“…A flow diagram describing this validation study is shown in Figure 1. The protocol for this population-based cohort study was published previously [15]. Briefly, the protocol describes a study in which the validity of a migration phenotype will be assessed, and a main study to be completed if the phenotype is found to be valid.…”
Section: Methodsmentioning
confidence: 99%